A retrospective multicenter study of sublingual gland carcinoma in Japan. Issue 1 (February 2020) - Kojima, Tsuyoshi; Hori, Ryusuke; Tanaka, Shinzo; Tamaki, Hisanobu; Asato, Ryo; Kitamura, Morimasa; Tateya, Ichiro; Shinohara, Shogo; Takebayashi, Shinji; Maetani, Toshiki; Kitani, Yoshiharu; Kumabe, Yohei; et al.
Abstract: Objective: Salivary gland carcinoma is rare among head and neck cancers. Sublingual gland carcinoma, a type of salivary gland carcinoma, is even rarer; therefore, the number of cases at a single institute is too small for sufficient evaluation of tumor characteristics. We conducted a multicenter, retrospective analysis of sublingual gland carcinomas in patients who visited 12 institutions associated with the Kyoto Hospital and Affiliated Facilities Head and Neck Clinical Oncology Group. Methods: Thirteen previously untreated patients who visited the institutions between 2006 and 2015 were enrolled. The overall survival (OS) and disease-free survival (DFS) rates for all patients and by disease stage were analyzed. Statistical analyses were performed for all patients with respect to disease stage. Results: Eight of thirteen patients were diagnosed with adenoid cystic carcinoma on pathological study. A significant difference in OS rate was observed between patients with Stage I–III and Stage IV disease; however, the difference in DFS rate by disease stage was not significant. Conclusion: Stage IV disease was identified as a poor prognostic factor in patients with sublingual gland carcinoma. However, even patients with Stage I–III disease experienced relatively short DFS. Distant metastasis is a serious problem among patients with sublingual gland carcinoma.